Appcelerator Titanium up and running - Anderson, John (O'Reilly Media, 2013)
Build native apps for iOS, Android, and Blackberry from a single JavaScript codebase with Appcelerator Titanium. This guide gets you quickly up to speed on this amazing framework and shows you how to generate cross-platform apps with 100% native controls. You'll also learn the advantages of using Titanium when you want to create an app for just one native platform, rather than struggle with Java or Objective-C. Fast-paced and full of examples, this book helps you build your first project with Titanium Studio, and then takes you through the steps necessary to build complex data-bound apps. Learn how Titanium differs from frameworks such as jQuery Mobile and Sencha Touch Set up and use iOS and Android SDKs and compilers with Titanium Build basic UI and window controls, and create your own composite objects Take a peek at how Titanium objects and methods work behind the scenes Learn how JavaScript makes Titanium easy to extend and customize Develop apps that consume complex data, whether it's stored locally or on remote servers Understand the pros and cons of distributing apps on the App Store and Android Market.
Print version record
Keywords: iOS (Electronic resource); Android (Electronic resource); Application software -- Development; Mobile computing -- Programming; IOS (Electronic resource); Logiciels d'application; Développement; Informatique mobile; Programmation; Application software; Development